2022
DOI: 10.1002/wjo2.6
|View full text |Cite
|
Sign up to set email alerts
|

The Draf III procedure: A review of indications and techniques

Abstract: The Draf Ⅲ procedure involves the creation of a common frontal sinus cavity. The most common indication for the Draf Ⅲ procedure is chronic rhinosinusitis of the frontal sinuses despite the failure of more conservative interventions such as bilateral Draf Ⅱa procedures. Primary Draf Ⅲ may be indicated in patients with a high risk of failures such as those with severe polyposis and those with a frontal sinus opening less than 4 mm on computed tomography imaging. Other indications for the Draf Ⅲ include access f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…In similar cases, the use of a Draf III with superior septectomy to create a common frontal sinus cavity and prophylactically prevent recurrence may be a preferred option for treatment. 10 In conclusion, this case illustrates the first unique occurrence of sequential presentations of frontal sinus pneumoceles, with the second developing after operative intervention on the first side. To our knowledge, this is the first case report to document such a phenomenon, which could only be possible secondary to the presence of 2 discrete frontal sinus cavities.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…In similar cases, the use of a Draf III with superior septectomy to create a common frontal sinus cavity and prophylactically prevent recurrence may be a preferred option for treatment. 10 In conclusion, this case illustrates the first unique occurrence of sequential presentations of frontal sinus pneumoceles, with the second developing after operative intervention on the first side. To our knowledge, this is the first case report to document such a phenomenon, which could only be possible secondary to the presence of 2 discrete frontal sinus cavities.…”
Section: Discussionmentioning
confidence: 64%
“…Our patient, however, presented with notable cosmetic deformities, making frontal sinus remodeling an appropriate treatment modality. In similar cases, the use of a Draf III with superior septectomy to create a common frontal sinus cavity and prophylactically prevent recurrence may be a preferred option for treatment 10 …”
Section: Discussionmentioning
confidence: 99%
“…For an exclusive endonasal approach, Gotlib et al [5] suggested Draf IIA or IIB when the lesion was limited to the fron- tal recess, and frontal sinus opacification was due to mucus retention. When the opening made by an initial Draf IIA procedure is insufficient to prevent postoperative stenosis and additional access is needed, Draf IIB is indicated [8]. When a lateralized middle turbinate has resulted from a previous Draf I or IIA procedure, Draf IIB is indicated for complete resection of the remnant middle turbinate, thus preventing narrowing of the frontal recess [8].…”
Section: Discussionmentioning
confidence: 99%
“…The most relevant shortcoming is mainly represented by the neo-ostium stenosis, which has been reported to occur up to 2 years following the Draf III procedure and leads to revision surgery in 5–30% of the time. [22 ▪▪ ] To overcome this major complication, most authors recommend achieving the maximal opening of the neo-ostium (approximately 21.0 mm × 19.5 mm), regular debridement of the sinusotomy as an in-office procedure as far as the compete mucosal healing of the surgical cavity, consistent intranasal steroid delivery and, most importantly, minimize the area of uncovered drilled bone by using specifically designed mucoperiosteal flaps to resurface the surgical areas. [23,24 ▪ ,25,26].…”
Section: Discussionmentioning
confidence: 99%